2014
DOI: 10.1016/j.trc.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and prediction of air traffic delays

Abstract: This paper presents a new class of models for predicting air traffic delays. The proposed models consider both temporal and spatial (that is, network) delay states as explanatory variables, and use Random Forest algorithms to predict departure delays 2-24 hours in the future. In addition to local delay variables that describe the arrival or departure delay states of the most influential airports and links (origin-destination pairs) in the network, new network delay variables that characterize the global delay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(156 citation statements)
references
References 14 publications
1
154
0
1
Order By: Relevance
“…Their findings revealed that the New York area is responsible for 15% of injected delays and 9% of propagated delays in the NAS. Rebollo and Balakrishnan used random forests and regression models to predict air traffic delays [20]. The authors examined their models using the 100 most frequently delayed links in the NAS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings revealed that the New York area is responsible for 15% of injected delays and 9% of propagated delays in the NAS. Rebollo and Balakrishnan used random forests and regression models to predict air traffic delays [20]. The authors examined their models using the 100 most frequently delayed links in the NAS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…6). This was designed so that the most important predictor had an importance of 100 (Rebollo, Balakrishnan 2014).…”
Section: Modelingmentioning
confidence: 99%
“…Many candidate scores can be used to compare two networks; their suitability can vary depending on the application being considered [17], [12]. For example, one can compare the edge weights of two graphs, that is, use the Euclidean distance between the vectors of edge weights as a measure of graph similarity [14]. However, such a representation requires O(n 2 ) parameters to represent a graph, where n is the number of nodes.…”
Section: Features For Comparing Networkmentioning
confidence: 99%
“…In contrast to previous work on delay propagation in air traffic networks [9], [10], our primary focus is not to cluster network nodes (airports) on the basis of their similarities, but instead, to cluster the networks themselves (i.e., the system state at different times) on the basis of their similarities [11], [12], [13]. In earlier work, the NAS delay state was characterized using the edge weights of the network; however, the connectivity and network structure of the system were not explicitly considered [14].…”
Section: Introductionmentioning
confidence: 99%